OCORRÊNCIA DOS GENÓTIPOS G E P DE ROTAVÍRUS DO GRUPO A EM BEZERROS DE REBANHOS DE CORTE NO ESTADO DE SÃO PAULO, BRASIL - Buzinaro, M.g. [UNESP] (2021)
The frequency of group A rotavirus and the molecular G and P characterization of strains in beef cattle were determined from July 2003 to July 2004, in herds of the state of São Paulo, Brazil. Samples came from 649 calves, aged between 1 and 60 days, from 14 beef cattle herds, regardless of clinical manifestation of diarrhea. A 64.3% (9/14) frequency of rotavirus among herds and 6.2% (40/649) among animals were detected by ELISA and polyacrylamide gel electrophoresis (PAGE). The higher frequency infection was detected in animals aged between 16 and 30 days (10.5%). Rotavirus infection was diagnosed in animals with (25.8%; 22/85) or without (3.2%; 18/564) clinical signs of diarrhea. A correlation was found between the presence of infection and the clinical manifestation of diarrhea (p < 0.05). PAGE analysis of the rotavirus’s genome profile identified 7 distinct electropherotypes which indicated extensive genomic diversity of the rotavirus in the region under analysis. Genotyping by polymerase chain reaction (RT-PCR) of the rotavirus strains revealed the genotypes G6P[5], G6P[11], G6P[5]P[11] and G10P[11].